Associations between blood ethylene oxide levels and serum neurofilament light chain concentrations in adults: evidence from the NHANES - Li, Shikun; Li, Wenchen; Liu, Jis Huang; Ma, Jing; Juan, Yan; Chen, Bo (Frontiers in Public Health, 2025)
BackgroundEthylene oxide (EO) is a widely used industrial chemical recognized for its health risks, potentially posing threats to human health, including neurotoxicity, cardiovascular damage, and carcinogenic effects. Neurofilament light chain (NfL) is a protein released into the blood following axonal damage. To date, no studies have investigated the relationship between EO exposure and NfL levels. Therefore, we selected 5,902,013–2014 National Health and Nutrition Examination Survey (NHANES) participants to examine the relationship between blood EO levels and serum NfL concentrations.MethodsAccording to the data from NHANES, this cross-sectional study used multiple regression analysis, subgroup analysis, and smooth curve fitting to explore the relationship between Ethylene oxide and Neurofilament light chain.ResultsThe results of the present study indicate a positive association between EO exposure and NfL concentrations. Greater EO exposure was correlated with increased serum NfL concentrations in the fully adjusted model [β = 0.28, 95% CI (0.16, 0.40)]. Each additional unit of EO exposure was linked to a 0.28-unit increase in the serum NfL level. Additionally, IN sensitivity analysis by changing EO exposure from a continuous variable to a categorical variable. The serum NfL concentrations increased with increasing tertiles of EO levels. Compared with the lowest tertile, the highest EO exposure tertile was associated with a 0.28-unit increase in serum NfL concentrations (β = 0.28, 95% CI 0.16, 0.40; P for trend = 0.0138).ConclusionOur results indicate a link between increased EO levels and higher serum NfL concentrations in a sample of US adults aged 20 years and older. Although the directionality and clinical significance of this observation remain uncertain, our results emphasize the importance of conducting additional studies to investigate the possible causes and neurological effects of exposure to EO in adults.